Methylglyoxal induces ambience for cancer promotion in HepG2 cells via Warburg effect and promotes glycation. Issue 10 (18th January 2022) - Sruthi, C R; Raghu, K. G.
Abstract: Methylglyoxal (MGO) is a toxic, highly reactive metabolite derived mainly from glucose and amino acids degradation. MGO is also one of the prime precursors for advanced glycation end products formation. The present research was performed to check whether MGO has any role in the promotion of cancer in HepG2 cells. For this, cells were incubated with MGO (50 µM) for 24 h and subjected to various analyses. Aminoguanidine (200 µM) was positive control. The various biochemical and protein expression studies, relevant to the MGO detoxification system, oxidative stress, and glycolysis were performed. MGO caused the reduction of expression of GLO 1 (27%) and GLO 2 (11%) causing weakening of the innate detoxification system. This is followed by an increase of RAGE (95%), AGEs or methylglyoxal adducts. We also observed hypoxia via estimation of oxygen consumption rate and surplus reactive oxygen species (ROS) (24%). To investigate the off‐target effect of MGO we checked its effect on glucose transport, and its associated proteins. Glucose uptake was found to increase (15%) significantly with overexpression of GLUT 1 (35%). We also found a significant increase of glycolytic enzymes such as hexokinase II, phosphofructokinase 1, and lactate dehydrogenase along with lactate production. Observation of surplus ROS and enhanced glycolysis led us to check the expression of HIF 1α which is their downstream signaling pathway. Interestingly HIF 1α was found to increase significantly (35%). It is known that enhanced glycolysis and oxidative stress are catalysts for the overexpression of HIF 1α which in turn creates an ambience for the promotion of cancer. Aminoguanidine was able to prevent the adverse effect of MGO partially. This is the first study to show the potential of MGO for the promotion of cancer in the non‐tumorigenic HepG2 cells via the Warburg effect and glycation.